Extraction Process, Component Analysis, and In Vitro Antioxidant, Antibacterial, and Anti-Inflammatory Activities of Total Flavonoid Extracts from Abutilon theophrasti Medic. Leaves - Chunlian Tian; Peng Zhang; Caixia Yang; Xiang Gao; Hong Wang; Yuru Guo; Mingchun Liu (Hindawi Limited, 2018)
The flavonoid fraction was extracted from the leaves of Abutilon theophrasti Medic., which are usually used as a traditional Chinese herbal medicine for the treatment of inflammation and joint pain. The current study focused on the extraction process, component analysis, and in vitro antioxidant, antibacterial, and anti-inflammatory activities of the flavonoid fraction as a part of ongoing research on bioactive substances from natural plant sources. This study evaluated the antioxidant activities via assays of DPPH radical scavenging capacity, ABTS radical scavenging capacity, and reducing power and investigated inhibitory activities against Escherichia coli, Salmonella, Staphylococcus aureus, and Streptococcus. Moreover, the inflammatory activity of the flavonoid fraction was estimated by measurement of the content of tumor necrosis factor alpha, interleukin-1-beta, interleukin-6, interleukin-10, nitric oxide, and cyclooxygenase-2 and the gene expression levels of several inflammation markers, such as inducible nitric oxide synthase and cyclooxygenase-2, in RAW 264.7 macrophages after LPS treatment. In addition, the underlying anti-inflammatory mechanisms, that is, the activation of nuclear factor kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways, were also revealed from the gene and protein expression levels. Taken together, these results suggested that the flavonoid fraction might exert in vitro antioxidant, antibacterial, and anti-inflammatory effects on LPS-stimulated RAW 264.7 macrophages and will be potentially useful as an adjuvant treatment for oxidative stress and bacterial and inflammatory diseases.